Strengthening proximal hip musculature for prevention of patellofemoral pain and ACL injuries in female football players. - Needs, N. A. (Journal of Australian Strength and Conditioning, 2017)
With respect to the female anatomy and lower limb injury, there is evidence that females exhibit greater knee valgus(4) and frontal and transverse plane motion at the hip during exercises such as stepping, landing and running(26). As one of the most participated female sports in the world, football (soccer) has seen a significant amount of serious lower limb injuries. Currently, female athletes are four to six times more likely to sustain a sports-related non-contact ACL injury than are male athletes(1). It is, therefore, important to focus on the prevention of non-contact injuries, specifically knee ACL sprains and patellofemoral pain, through implementation of programs that focus on landing technique, force reduction and overall strength and power qualities. PubMed and Google Scholar were used in the search for studies that focused on preventative measures for lower limb injuries in female football players and these studies have been analysed to construct a protocol that practicing Strength and Conditioning coaches may utilize to address functional asymmetries predictive of injury(8). In particular, isolated hip-abductor and rotator strengthening exercises combined with plyometrics-based movements and dynamic stabilization may be of benefit for strengthening proximal hip musculature in female football players and may decrease their risk of non-contact lower limb injury.